HOUSEHOLD LEADERSHIP FROM NATURE TO NURTURE: DISMANTLING QIWAMAH IN Q.S. AN-NISA': 34 - Tahnia Basrah; Hamka Hasan; Nur Arfiyah Febriani (TAFASIR: Journal of Quranic Studies, 2025)
Abstract This research discusses the interpretation of An-Nisa verse 34, which was previously understood through nature theory and is now examined through nurture theory. The research methodology employs library research, involving the reading of literature related to the research theme such as books, journals, and other scholarly works. Since this is library research, the methods used are descriptive and comparative. The research findings show that not all mufassir (Quranic commentators) interpret the verse regarding leadership as being exclusively and specifically for men; rather, there are certain conditions where women who possess the potential and capability are permitted to become leaders, because there are circumstances where women have the competence to be leaders, including within the household. Keywords: Nature, Nurture, Leadership, Women